Aerial Robots Aerodynamics, Control and Applications - Dario Lopez Mejia, Omar; Alberto Escobar Gomez, Jaime (IntechOpen, 2017)
Few years ago, the topic of aerial robots was exclusively related to the robotics community, so a great number of books about the dynamics and control of aerial robots and UAVs have been written. As the control technology for UAVs advances, the great interaction that exists between other systems and elements that are as important as control such as aerodynamics, energy efficiency, acoustics, structural integrity, and applications, among others has become evident. Aerial Robots - Aerodynamics, Control, and Applications is an attempt to bring some of these topics related to UAVs together in just one book and to look at a selection of the most relevant problems of UAVs in a broader engineering perspective.